PENGEMBANGAN WESALJU (WEBSITE SALAT JUMAT) BERBASIS GOOGLE SITES DALAM PEMBELAJARAN PAI KELAS 4 - Haidar Akmal Ghifari; Syifa Fauziyah; Via Siti Fatimah; Ani Nur Aeni (Institut Agama Islam Hamzanwadi NW Lombok Timur, 2025)
Many elementary school students, especially those in grade 4, lack understanding of the implementation of Friday prayer. This issue has drawn the attention of parents, teachers, and the community. One contributing factor is the monotonous and uninspiring learning process, which leads to student boredom. To address this, learning should be made more engaging by integrating technology-based media. The goal is not only to update teaching methods but also to introduce students to the benefits of technology and increase their motivation to learn. This study aims to help students better understand the concept of Friday prayer, which is obligatory for every Muslim male who has reached puberty. By understanding the core material, students are expected to realize that neglecting Friday prayer is something that should be avoided. One solution developed is the WESALJU (Website Salat Jumat) learning media based on Google Sites. The research method used is Research and Development (R&D) with the ADDIE approach, consisting of Analysis, Design, Development, Implementation, and Evaluation. The results of the student questionnaire showed a validity score of 87.16%, categorized as very valid. Therefore, WESALJU has been proven effective in increasing students' awareness and understanding of the importance of Friday prayer.